Variations of the cubital superficial vein investigated by using the intravenous illuminator - Lee, Hyunsu (Anat Cell Biol, 2015)
The purpose of this study was to report variations of the cubital superficial vein patterns in the Korean subjects, which was investigated by using venous illuminator, AccuVein. The 200 Korean subjects were randomly chosen from the patients and staff of the Keimyung University Dongsan Medical Center in Daegu, Korea. After excluding the inappropriate cases for detecting venous pattern, we collected 174 cases of right upper limbs and 179 cases of left upper limbs. The superficial veins of the cubital fossa were detected and classified into four types according to the presence of the median cubital vein (MCV) or median antebrachial vein. The type II, presenting the both cephalic and basilic vein connected by the MCV, was most common (177 upper limbs, 50.1%). Although the most common type in male and female was different as type I (108 upper limbs, 49.3%) and type II (75 upper limbs, 56.0%), respectively, statistical significance was not detected (P=0.241). The frequency of the each types between right and left upper limbs was also not different (P=0.973). Among 154 subjects who were observed the venous pattern in the both upper limbs, 76 subjects (49.3%) had the same venous pattern. Using AccuVein to investigate the venous pattern has an advantage of lager scale examination compared to the cadaver study. Our results might be helpful for medical practitioner to be aware of the variation of the superficial cubital superficial vein.